TATA KELOLA PERUSAHAAN, STRUKTUR KEPEMILIKAN DAN VOLATILITAS ARUS KAS TERHADAP PERSISTENSI LABA - Anfas Anfas; Zainuddin Zainuddin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2022)
This research aims to analyze and test the influence of the board of commissioners, audit committee, family ownership, institutional ownership and cash flow volatility on profit persistence in manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The sample in this study was 21 companies with 105 observations. Sampling techniques use purposive sampling methods. Data analysis techniques use multiple linear regression analysis with the help of eviews software. The results showed that institutional ownership had a positive effect on profit persistence, and audit committees negatively affected profit persistence, while a board of commissioners, family ownership and cash flow volatility had no impact on profit persistence.